2021
DOI: 10.3889/oamjms.2021.5720
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potentiality of Family Resources on Basic Household Sanitation Management in Dense Settlements of Binjai in North Sumatera Province of Indonesia

Abstract: BACKGROUND: Community empowerment-based sanitation development by prioritizing participation has been implemented; however, it still shows insignificant progression. Even though the family is the manager of basic sanitation starting from the household, personal empowerment, and family participation miss from the focus of attention. AIM: This study thus aimed to develop a participatory model of family empowerment in the management of basic sanitation at the household level. METHODS: This type of qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Waste reduction was focused on sorting waste and was considered to be able to reduce the amount of existing waste volume [12]. The previous research on basic sanitation conducted in Binjai, shown that waste management wich is one of the basic sanitation management models can be improved based on participatory family empowerment by employing assistance and the division of tasks to family members [13].…”
Section: Discussionmentioning
confidence: 99%
“…Waste reduction was focused on sorting waste and was considered to be able to reduce the amount of existing waste volume [12]. The previous research on basic sanitation conducted in Binjai, shown that waste management wich is one of the basic sanitation management models can be improved based on participatory family empowerment by employing assistance and the division of tasks to family members [13].…”
Section: Discussionmentioning
confidence: 99%